The Test Instrument of Senior High School Critical Thinking Skills on Human Excretory System Materia (FMIPA UNNES, 2022)
The purpose of this study was to develop a suitable test instrument to measure the critical thinking skills of high school students on the material of the human excretory system. The research method used, namely Research and Development (R&D). The model used in developing this instrument was adapted from the stages according to Sugiyono (2015) with ten stages, namely potential and problems, data collection, product design, design validation, design revision, smallscale test, product revision I, large-scale test, product revision. II, and final product review. The test subjects in this study were students of class XI MIPA SMA Negeri 1 Juwana. Data collection techniques using tests and questionnaires. The test instrument refers to the Facione indicators (interpretation, analysis, inference, evaluation, explanation and analysis). self- regulation ) in the form of a description of 18 items to measure students' critical thinking skills, while a questionnaire was used to collect data from students' responses to the instruments that had been prepared. Student questionnaires are made using a scale Likert . Analysis of the data used for the test in the form of tests of validity, reliability, level of difficulty, and distinguishing power using the SPSS program version 20. Based on the results of the small-scale test of 18 questions, as many as 3 items are not valid so that improvements must be made. Students' critical thinking skills on the small-scale test are included in the high category with a percentage of 48.5%. In the large-scale test, 18 items have been declared valid and feasible to use and 52.3% of students' critical thinking skills are included in the high category. The conclusion of the research is that the instrument is declared valid and feasible to use based on expert validation, item analysis and field trials and the level of critical thinking skills of SMA Negeri 1 Juwana students is in the high category.